The increased purchase of asthma medication for individuals born preterm seems to wane with age: A register-based longitudinal national cohort study. - Anne Louise de Barros Damgaard; Rasmus Gregersen; Theis Lange; Frederik Buchvald; Bo Mølholm Hansen; Gorm Greisen (PLoS ONE)
Introduction Preterm birth is associated with increased risk of respiratory symptoms in childhood, often treated with asthma medication. We designed a follow-up study to previous research and investigated whether the association of gestational age with purchasing asthma medication diminishes in adulthood. Methods We conducted a register-based study of a national cohort of all infants born in Denmark in 1980-2009 evaluating longitudinal data on individually prescribed asthma medication (both inhaled ß-2 receptor agonist and different controller treatment over 2-year periods) available from 1995-2011. We analyzed the effect of gestational age considering age, birth year, and perinatal variables using logistic regression with a Generalized Estimating Equations model. All data were unambiguously linked through the Civil Registration System. Results We included 1,819,743 individuals in our study population. We found an inverse dose-response relationship between gestational age and asthma medication in earlier age-groups with a gradual decrease in odds ratios with increasing age and loss of statistical significance in early adulthood (18-31 years). For our oldest generations, there was a significant effect of gestational age (p-value = 0.04), which became insignificant when adjusting for confounding and mediating factors (p = 0.44). There were significant interactions between gestational age and age (p<0.0001) and gestational age and birth year, but these were most important during childhood (0-11 years) and for our youngest generations (born after 1995). Conclusion The strong association between gestational age and purchase of prescription asthma medication weakens with age into early adulthood, in consistence with the results from our previous study. The risk for purchasing medication to treat asthma-like symptoms was higher in more recent birth years, but the effect of gestational age was small beyond 11 years of age. Gestational age per se did not seem to be significant for the development of asthma-like symptoms: most of its effect could be explained by other perinatal factors.